Pengaruh Model Cooperative Learning Tipe Stad Terhadap Hasil Belajar Siswa Mata Pelajaran Ekonomi Kelas Xi IPS 2 di SMA Negeri 1 Telaga Kecamatan Telaga Kabupaten Gorontalo - Rahmad Rifan Suna; Sudirman (Jurnal Pendidikan Ekonomi dan Bisnis, 2024)
The purpose of the study was to determine the effect of the STAD-type cooperative learning model on economic learning outcomes of 61 students of class XI social sciences 2 at SMA 1 state senior high school in Telaga, Telaga district, Gorontalo regency. All data of this quantitative research were collected from observations, questionnaires, and interviews. These data were further analyzed using a simple linear regression data analysis. The results reveal that the STAD-type cooperative model positively and significantly affects the students' learning outcomes. The more often the STAD- type cooperative model is applied, the more it will improve students' learning outcomes. The STAD-type cooperative model is one of the most critical learning models in determining learning outcomes. The quantity and influence of the STAD model contribute 48.2% to the variables of student learning outcomes. In comparison, the other 51.8% is influenced by factors outside the variables studied, namely other cooperative learning models.